THE ORIGIN AND EVOLUTION OF FEUDALISM AND IMPACTS IN PAKISTAN; A CASE STUDY OF DERA GHAZI KHAN 1947-2020 - Dr. Sohail Akhtar; Iqra Nazeer; Nida Fatima; Ushbah Amjad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Feudalism is not a new phenmenon of society, actually it is an ancient issue of the humanity. The term feudalism was started from Europe in medival period during the decline of Roman empire. The continuous wars between Great Britain and France divided the people and stratification of society appeared in Europe. Feudalism was very close to the policy of divide and rule. In 1857 colonial Government established in India and they also exercised the same in Subccontinent. They won the Second Sikh War in 1849 and with the annexation of Punjab they became the ruler of entire India.Allthough their extention policy, they marched toward the west of Indus in 1839 regarding great game. During forward policy, they tried to engage the Baloch tribes. Therefore, they granted and obliged the various tribal heads of Dera Ghazi Khan. But after 1854 when they marched in Balochistan they faced a strong and powerful resistance in the tribal belt of Dera Ghazi which was an important route and area before Balochistan.The continuel resistanse forced the colonial government to negociate with tribes. In this regard Robert Sundeman was given the Task to manage these tribes and after mutual discussion in 1866 Sundeman became successful to form the Tumandari system in Dera Ghazi Khan.The tribal Chief was appointed as a Tumandar. This Tumandari system was infact a feudalism. Fuedal lords are very powerful in their territorial authority. This paper highlights the socio-political impacts of the feudalism on the society oof Dera Ghazi Khan.